An investigation on the effectiveness of cutting employee related costs as a performance measure: a case of Damofalls Investments - Madzima, Lionel (Midlands State University, 2018)
The research was carried out to evaluate the effectiveness of cutting down on employee related costs on the viability and performance of the organization as exercised by Damofalls Investments. This was lined with the background that the company was experiencing increasing costs and on the other hand declining profits. So this arose the need for the company to try and cut costs to maintain a standing ground in the construction industry. The research sought to evaluate the current employee cost cutting measures employed, identify other aspects that can lead to improvement in the company’s viability, monitor and assess the reaction of employees on the measures implemented, establish challenges which could be encountered in implementing the cost control measures and establishing the best practice which can be adopted. A case study research design was used in this study making use of questionnaires, interviews as well as secondary data for data collection. These techniques gave research findings which were analysed for the satisfaction of the objectives of the research. Based on the findings, it was realized that cutting employee related costs hinders productivity and negatively affects the business opportunities of an organization. It was deduced that the company engaged in cost cutting measures which led to the demotivation of employees resulting in company performance declining. The research highlighted that there is need for Damofalls to consider all the processes and services inside the company (Activity Based Costing) for cost saving opportunities and can also consider reviewing cost control as a continuous practice.